Attitudes and barriers to the use of donation after cardiac death livers: Comparison of a United States transplant center survey to the united network for organ sharing data. Issue 11 (26th October 2017) - Sher, Linda; Quintini, Cristiano; Fayek, Sameh Adel; Abt, Peter; Lo, Mary; Yuk, Pui; Ji, Lingyun; Groshen, Susan; Case, Jamie; Marsh, Christopher Lee
Abstract : Transplantation of liver grafts from donation after cardiac death (DCD) is limited. To identify barriers of DCD liver utilization, all active US liver transplant centers (n = 138) were surveyed, and the responses were compared with the United Network for Organ Sharing (UNOS) data. In total, 74 (54%) centers responded, and diversity in attitudes was observed, with many not using organ and/or recipient prognostic variables defined in prior studies and UNOS data analysis. Most centers (74%) believed lack of a system allowing a timely retransplant is a barrier to utilization. UNOS data demonstrated worse 1‐ and 5‐year patient survival (PS) and graft survival (GS) in DCD (PS, 86% and 64%; GS, 82% and 59%, respectively) versus donation after brain death (DBD) recipients (PS, 90% and 71%; GS, 88% and 69%, respectively). Donor alanine aminotransferase (ALT), recipient Model for End‐Stage Liver Disease (MELD), and cold ischemia time (CIT) significantly impacted DCD outcomes to a greater extent than DBD outcomes. At 3 years, relisting and retransplant rates were 7.9% and 4.6% higher in DCD recipients. To optimize outcome, our data support the use of DCD liver grafts with CIT <6‐8 hours in patients with MELD ≤ 20. In conclusion, standardization of donor and recipient criteria, defining the impact of ischemic cholangiopathy, addressing donor hospital policies, and developing a strategy for timely retransplant may help to expand the use of these organs. Liver Transplantation 23 1372–1383 2017 AASLD.